Urgency Fee Based Income of Banking Industries in The New Normal - Lucky Nugroho; Surender Mor; Yananto Mihadi Putra; Budhi Pribadhi Ishak; Nurhasanah (Baca Dulu Publisher, 2024)
This study aims to analyze the net profit growth of the banking sector based on their core business, namely credit growth and growth in third-party fundraising in the period before the Covid 19 pandemic and during the Covid-19 pandemic. Meanwhile, bad debt growth is a moderating variable factor. The method used in this study is quantitative with moderating regression analysis with a sample of 34 banks. The results of this study are in the period before the Covid-19 pandemic and during the Covid-19 pandemic, where the growth of third-party funds had a positive and significant effect on net profit growth, credit growth moderated by bad debt growth had a positive and significant effect on net profit growth, growth in third-party funds moderated by the growth of bad debt has a positive and significant effect on net profit growth. However, there are differences in the effect of credit growth on net profit growth in the period before the Covid-19 pandemic, which has a positive and significant effect. Meanwhile, during the Covid-19 pandemic, credit growth had an insignificant positive effect on net profit growth. In addition, based on the determination test, during the Covid-19 pandemic, the influence of credit growth, third-party funds growth, and bad debt were not the main contributors to net profit growth. This is because, during the Covid-19 pandemic, bank profit growth was dominated by fee-based income. The implication of this research is to identify bank business prospects in the new normal period, which is dominated by fee-based income, so the banking industry must invest in developing digital banking to increase its profit. This study identifies that the banking industry's business in the new normal era has excellent prospects if it can change its business strategy from credit to fee-based income.